Understanding the nature of medication adherence issues with the HIV infected patient in the family practice setting - Prutch, Peter Thomas, author; Banning, James H., advisor; Quick, Donald Gene, advisor; Buchan, Victoria V., committee member; Kaminski, Karen, committee member (Colorado State University. Libraries, 2005)
One of the greatest challenges in managing the medication therapy in any chronic disease is how to influence human behavior, such as adherence to antiretroviral therapy in the Human Immune Virus (HIV) positive patient. Although data demonstrate significant viral suppression and immunologic benefits of therapy when taking antiretroviral medication at a 95% adherence, non-adherence remains a problem in the HIV or Acquired Immune Deficiency Syndrome (AIDS) population. Past literature indicates it may relate to the quality of information given, the impact of the regimen on daily life, the physical or the incapacity of patients, or their social isolation. This is a basic qualitative research study. The purpose of this study is to have a basic interpretive qualitative understanding of the nature of non-adherence to mediation in the HIV infected patient in a family practice setting. During interviewing, each participant had their own personal story about being HIV positive and why they adhere or do not adhere to their medication regimen. It appears that adherence to any highly active antiretroviral therapy (HAART) revolves around the well being and the understanding of lifelong commitment of the HIV patient. A hypothetical model has been constructed relating the Health Belief Model to HIV medication adherence as found in this study. The educational opportunities for the HIV infected person have improved over the past 10 years. Many private and government organizations provide training and learning materials and the healthcare providers are more aware of the needs of the HIV positive person. The lifestyles of HIV positive people are no different then the non-infected person. However, the side effects of the HAART have been shown to affect the adherence. Seeing HIV in a more positive light contributes to the well being of the infected person. Patients find it easier to cope with their disease if they see it as an opportunity for personal growth or can attach some other positive meaning to it. The outlook on HIV disease has gone from a death sentence to one of guarded optimism. It is viewed as a life long commitment.
Keywords: HIV-positive persons; Patient compliance